O mix público e privado no sistema de saúde brasileiro: coexistência em evidência - CARDOSO, Márcia Roberta de Oliveira (Associação Brasileira da Rede UNIDA, 2023)
This article aims to describe and analyze the main nuances of the public and private relationship in the Brazilian health system. In this sense, in addition to presenting a discussion on public and private concepts, characteristics, trends and impacts of the public-private mix in the Brazilian health system will also be punctuated. A bibliographic survey was carried out in the form of a narrative review on the classical and current production of scientific articles, dissertations, theses and research reports that presented pertinent reflections on the topic in the last ten years. The results were categorized in the following axes: Considerations about the concepts of public and private; Characteristics of the Brazilian Health System; Trends and Impacts of the Public-Private Mix in the Brazilian Health System. It was clear the existence of a conceptual polysemy on the public and private terms and due to the arrangements between these two dimensions in the structure of the Brazilian health system, it is based on the premise that it is a mixed system, where the public sector And the private sector coexist in the provision, financing, demand and use of health services. Within this context, problems of the systems with duplicate coverage were found, with impacts on equity, financing, production, use and access to health services. Therefore it is urgent to create strategies and mechanisms of resistance that guarantee an integrated regulatory action for a National Health System that, among other things, defines the public / private relation, besides the need to integrate public policies, not only aimed at For development, but also for well-being.